2021
DOI: 10.1111/cdoe.12671
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck cancer in Cali, Colombia: Population‐based study

Abstract: Head and neck cancer (HNC) is the seventh most common type of cancer in the world, mainly affects men, and includes a heterogeneous group of malignant neoplasms in the upper aerodigestive tract. 1,2 HNC affects the oral cavity, oropharynx, salivary glands, paranasal sinuses, nasopharynx, hypopharynx and larynx. 3 Worldwide, it is estimated that 500 000 new cases are diagnosed annually, two-thirds of them are happening in developing countries and that 300 000 will die from the disease. 3,4 Depending on the popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…World Health Organization has recently noted that oral cancers are to be given priorities. Maxillofacial and neck tumors exist at an increased frequency in humanity, with an incidence rate of 500,000 new patients yearly ( Aragón et al, 2022 ). Although head and neck tumors in children are of a low incidence, the line of treatment, anticipation and prognosis should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…World Health Organization has recently noted that oral cancers are to be given priorities. Maxillofacial and neck tumors exist at an increased frequency in humanity, with an incidence rate of 500,000 new patients yearly ( Aragón et al, 2022 ). Although head and neck tumors in children are of a low incidence, the line of treatment, anticipation and prognosis should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that the 5-year survival rate for HNC is approximately 40-50% and accounts for 3% of cancer-related deaths after medical treatments. [1][2][3] The main effective treatment options for HNC include surgery, chemotherapy, radiation therapy, targeted therapy, and immunotherapy. The advancement of treatments improved HNC outcomes in the recent decade.…”
Section: Introductionmentioning
confidence: 99%
“…Head and neck cancer (HNC), including oral cavity, oropharyngeal, hypopharyngeal, and laryngeal tumors, is the seventh most common type of cancer worldwide. Recent studies have reported that the 5‐year survival rate for HNC is approximately 40–50% and accounts for 3% of cancer‐related deaths after medical treatments 1–3 . The main effective treatment options for HNC include surgery, chemotherapy, radiation therapy, targeted therapy, and immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The crude incidence rate was 8.32/100,000 (2). With recent advances in cancer treatment and HNC management, the 5-year survival rate of HNC is estimated as 40-50% (3,4). Financial toxicity is a significant issue for some HNC patients, which is associated with a reduced health-related quality of life (5).…”
Section: Introductionmentioning
confidence: 99%